Evaluation of a West Australian residential mental health respite service. (18th January 2018) - Gillieatt, Sue; Martin, Robyn; Dorozenko, Kate P.; Munro, Adrian
Abstract: Family members continue to be the predominant providers of support, care and accommodation for loved ones with mental health issues, and empirical studies suggest that accessing mental health respite can be helpful for both carers and consumers. However, the availability of, and access to, this respite in Australia is far from optimal. Major issues have also been identified such as low utilisation, the inappropriate and inflexible nature of services and the inability of services to respond to situations where multiple needs exist. This article presents findings from a small evaluation of a pilot residential respite service. Semi‐structured interviews were conducted with eight family members/carers and four consumers using the service, and five service providers. In addition, anonymised sociodemographic information about all users of the service in the first 9 months of its operation were analysed. Reflecting the current limitations around respite options, the majority of family members/carers and consumers were appreciative of, and satisfied with, the service. The research highlighted issues such as availability and suitability of respite, particularly when consumers had multiple and unmet needs. Mental health residential respite is often a stopgap in crisis situations and intersects with the difficulty of planning respite and shortages in affordable supported accommodation. Furthermore, the ramifications of individualised funding for people with "psychosocial disability" in the new Australian National Disability Insurance Scheme (NDIS) remain unclear. While family members and carers may benefit indirectly from NDIS funding, it is especially important at this time that the need for more suitable, recovery‐oriented respite services is highlighted.